2014
DOI: 10.1007/978-3-319-07626-3_5
|View full text |Cite
|
Sign up to set email alerts
|

A Usability Study on Elder Adults Utilizing Social Networking Sites

Abstract: for being so flexible with my schedule. I also want to thank my newer co-workers and friends Claire Snodgrass, Lauren Hoffen, and Andy Smith for their warm smiles and for always letting me vent when I felt I could not go any further.With love, I thank you all, my dear friends and family, for believing in me.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
(99 reference statements)
0
20
1
6
Order By: Relevance
“…Therefore, our findings are in line with previous studies which concluded that as users became familiar with an interface, they considered it more usable because they could locate functions more easily. 39 We can conclude that website and interface usability improve with increased familiarity, as users become less and less frustrated with the system because they can locate and use functions more quickly and easily with time.…”
Section: Gendermentioning
confidence: 99%
“…Therefore, our findings are in line with previous studies which concluded that as users became familiar with an interface, they considered it more usable because they could locate functions more easily. 39 We can conclude that website and interface usability improve with increased familiarity, as users become less and less frustrated with the system because they can locate and use functions more quickly and easily with time.…”
Section: Gendermentioning
confidence: 99%
“…These activities will be defined into major task categories and then divided into sub-task activities, similar to previous research conducted by Arfaa & Wang (2014). These activities will be defined into major task categories and then divided into sub-task activities, similar to previous research conducted by Arfaa & Wang (2014).…”
Section: Methodsmentioning
confidence: 96%
“…Cada vez más adultos mayores usan ordenadores e Internet, sin embargo, su presencia en las redes sociales sigue siendo baja en comparación con los más jóvenes (Anderson & Perrin, 2017;Arfaa & Wang, 2014;Sims, Reed, & Carr, 2016;Vošner, Bobek, Kokol & Krečič, 2016); no han adoptado este medio de comunicación tan rápido como estos últimos (Braun, 2013;Madden, 2010). Se encuentra una brecha cultural generacional en la forma en que las personas jóvenes y las personas mayores experimentan las redes sociales (Lüders & Brandtzaeg, 2017).…”
Section: Las Personas Mayores Como Usuarias De Internet Y Redes Sociaunclassified
“…Se están dando diferentes respuestas a cuáles son las razones para que los mayores no utilicen las redes sociales tales como: dificultad de uso de los sitios de redes sociales debido a la falta de experiencia y competencia en ordenadores y a los problemas de formato, navegación y diseño (Arfaa & Wang, 2014); los mayores no usuarios de redes sociales perciben la comunicación en ellas como fría y narcisista, ven que su utilidad es baja y la preocupación por la privacidad y seguridad también es frecuente (Lüders & Brandtzaeg, 2017); muchos simplemente no tienen confianza en su propia capacidad para aprender y utilizar correctamente los dispositivos electrónicos (Anderson & Perrin, 2017).…”
Section: Las Personas Mayores Como Usuarias De Internet Y Redes Sociaunclassified